Lin28 is induced in primed embryonic stem cells and regulates let‐7‐independent events. Issue 3 (5th December 2016) - Parisi, Silvia; Passaro, Fabiana; Russo, Luigi; Musto, Anna; Navarra, Angelica; Romano, Simona; Petrosino, Giuseppe; Russo, Tommaso
ABSTRACT: Lin28 RNA‐binding proteins play important roles in pluripotent stem cells, but the regulation of their expression and the mechanisms underlying their functions are still not definitively understood. Here we address the above‐mentioned issues in the first steps of mouse embryonic stem cell (ESC) differentiation. We observed that the expression of Lin28 genes is transiently induced soon after the exit of ESCs from the naive ground state and that this induction is due to the Hmga2‐dependent engagement of Otx2 with enhancers present at both Lin28 gene loci. These mechanisms are crucial for Lin28 regulation, as demonstrated by the abolishment of the Lin28 accumulation in Otx2‐or Hmga2‐knockout cells compared to the control cells. We have also found that Lin28 controls Hmga2 expression levels during ESC differentiation through a let‐7‐independent mechanism. Indeed, we found that Lin28 proteins bind a highly conserved element in the 3′ UTR of Hmga2 mRNA, and this provokes a down‐regulation of its translation. This mechanism prevents the inappropriate accumulation of Hmga2 that would modify the proliferation and physiological apoptosis of differentiating ESCs. In summary, we demonstrated that during ESC differentiation, Lin28 transient induction is dependent on Otx2 and Hmga2 and prevents an inappropriate excessive rise of Hmga2 levels.—Parisi, S., Passaro, F., Russo, L., Musto, A., Navarra, A., Romano, S., Petrosino, G., Russo, T. Lin28 is induced in primed embryonic stem cells and regulates let‐7‐independent events. FASEB J. 31, 1046–1058 (2017). www.fasebj.org